Penerapan Sertifikasi Halal pada Kuliner UMKM Kecamatan Burneh Kabupaten Bangkalan dalam Pengelolaan Sumber Daya Manusia - Jamilatul Hasanah; Wilda Al Aluf; Surya Andhika Putra; Iriani Ismail (JURNAL RISET MANAJEMEN (JURMA), 2024)
In general, every job has a goal, the goal will be achieved after the activity is completed. Likewise, this research also has goals to be achieved. This study aims to determine the implementation of halal certification in culinary MSMEs in Burneh Bangkalan district and identify factors that support and hinder the implementation of halal certification in culinary MSMEs in Burneh Bangkalan district. In addition, this research is also expected to bring benefits in the form of knowledge and insight to the wider community in achieving halal certification according to Islamic teachings. This research was conducted based on descriptive qualitative research methods. The data collection techniques used include interviews with information providers (MSME actors) as a source of information.